2018
DOI: 10.15252/emmm.201809456
|View full text |Cite
|
Sign up to set email alerts
|

Alternative oxidase‐mediated respiration prevents lethal mitochondrial cardiomyopathy

Abstract: Alternative oxidase (AOX) is a non‐mammalian enzyme that can bypass blockade of the complex III‐IV segment of the respiratory chain (RC). We crossed a Ciona intestinalis AOX transgene into RC complex III (cIII)‐deficient Bcs1l p.S78G knock‐in mice, displaying multiple visceral manifestations and premature death. The homozygotes expressing AOX were viable, and their median survival was extended from 210 to 590 days due to permanent prevention of lethal cardiomyopathy. AOX also prevented renal tubular atrophy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 58 publications
6
95
0
Order By: Relevance
“…To rule out the possibility that the period of anoxia was not sufficient, we replicated the experiments with an extended period of anoxia (30 minutes), which essentially gave the same results (Figure B‐E). Together with previous findings of AOX activity in the heart under various conditions, we concluded that a functional impairment of AOX is an unlikely explanation for the lack of cardioprotection against I/R injury, and that, therefore, all observed phenomena can mechanistically be attributed to catalytic AOX activity interfering with the mitochondrial respiratory chain and specifically to the restoration of the electron flux through the ETC.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…To rule out the possibility that the period of anoxia was not sufficient, we replicated the experiments with an extended period of anoxia (30 minutes), which essentially gave the same results (Figure B‐E). Together with previous findings of AOX activity in the heart under various conditions, we concluded that a functional impairment of AOX is an unlikely explanation for the lack of cardioprotection against I/R injury, and that, therefore, all observed phenomena can mechanistically be attributed to catalytic AOX activity interfering with the mitochondrial respiratory chain and specifically to the restoration of the electron flux through the ETC.…”
Section: Resultssupporting
confidence: 82%
“…To rule out the possibility that the period of anoxia was not sufficient, we replicated the experiments with an extended period of anoxia (30 minutes), which essentially gave the same results ( Figure S1B-E). Together with previous findings of AOX activity in the heart under various conditions, 33,38,40 we concluded that a functional…”
Section: Aox Is Catalytically Active In Post-anoxic Heart Mitochondriasupporting
confidence: 88%
See 1 more Smart Citation
“…In accordance with this, the ubiquitous expression of Ciona AOX in both flies (Fernandez‐Ayala et al, ) and mammals (Szibor et al, ) has almost no detectable physiological effect under nonstressed conditions. However, if the standard respiratory chain is dysfunctional, for example, due to toxic inhibition (El‐Khoury et al, ; Fernandez‐Ayala et al, ; Szibor et al, ), overload (Mills et al, ), or genetic damage (Kemppainen et al, ; Rajendran et al, ), AOX is able to compensate the resulting phenotypes to a significant degree. However, since AOX bypasses two of the proton‐pumping steps of the standard respiratory chain, it is not able to fully restore ATP production.…”
Section: Introductionmentioning
confidence: 99%
“…The sea squirt alternative oxidase (AOX) is able to bypass the distal part of the MRC and was shown to alleviate the consequences of CIII and CIV defects in several cellular and Drosophila models. In this issue of EMBO Molecular Medicine, Rajendran et al (2019) demonstrate the first proof of concept in mammals, by showing that AOX is capable to extend lifespan and prevent heart failure in a CIII deficient mouse model, raising the possibility of future human AOX bypass treatment. EMBO Mol Med (2019) 11: e9962 See also: J Rajendran et al (January 2019) M itochondria are intracellular organelles with a separate genome (mtDNA) and translation system, present in all enucleated cells.…”
mentioning
confidence: 99%